1994
DOI: 10.1128/jb.176.5.1383-1389.1994
|View full text |Cite
|
Sign up to set email alerts
|

Role of the delta subunit in enhancing proton conduction through the F0 of the Escherichia coli F1F0 ATPase

Abstract: We studied the effect of the 8 subunit of the Escherichia coli F1 ATPase on the proton permeability of the Fo proton channel synthesized and assembled in vivo. Membranes isolated from an unc deletion strain carrying a plasmid containing the genes for the Fo subunits and the 8 subunit were significantly more permeable to protons than membranes isolated from the same strain carrying a plasmid containing the genes for the Fo subunits alone. This increased proton permeability could be blocked by treatment with eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Furthermore, purification of F O subunits and reconstitution into liposomes revealed the same characteristics (51,52). In contrast, after synthesis of F O subunits in the absence of F 1 , only low levels of proton permeability were observed in membranes as well as after reconstitution into liposomes, implying a dependence on F 1 for the proton translocation by F O (53,54), although the additional presence of subunit ␦ enhances the proton conduction through F O (55,56).…”
Section: Time-delayed In Vivo Assembly Of Subunit ␦ Into Preformed F mentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, purification of F O subunits and reconstitution into liposomes revealed the same characteristics (51,52). In contrast, after synthesis of F O subunits in the absence of F 1 , only low levels of proton permeability were observed in membranes as well as after reconstitution into liposomes, implying a dependence on F 1 for the proton translocation by F O (53,54), although the additional presence of subunit ␦ enhances the proton conduction through F O (55,56).…”
Section: Time-delayed In Vivo Assembly Of Subunit ␦ Into Preformed F mentioning
confidence: 94%
“…However, whether subunit ␦ simply increases the affinity of ab 2 for the rest of the complex or whether it changes the conformation of F O to an active one, as suggested previously (55,56), remains to be solved in further investigations.…”
Section: Time-delayed In Vivo Assembly Of Subunit ␦ Into Preformed F mentioning
confidence: 99%
“…In subsequent work, Brusilow and co-workers (53,54) demonstrated that the ␦ subunit was required for the formation of the proton pore from the cloned F 0 subunits. Here we have shown that the same region of b implicated in the F 0 assembly process is essential for binding to ␦, strengthening the argument that the b-␦ interaction is critical for the assembly of functional F 0 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, purification of F o subunits from assembled F o F 1 and their reconstitution into liposomes revealed the same characteristics [5,56]. In contrast, after synthesis of F o subunits in the absence of F 1 , only low levels of proton permeability were observed in membranes as well as after reconstitution of purified subunits into liposomes, implying a dependence on F 1 for the proton translocation by F o [15,16], although the additional presence of subunit δ slightly enhances the proton conduction through F o [57,58]. The interdependence between F o and F 1 during assembly has been proposed to ensure that an open proton channel does not exist as an intermediate [59,16].…”
Section: Generation Of the Proton-translocating F O Complexmentioning
confidence: 99%